Fabry's Disease with LVOT Obstruction: Diagnosis and Management. Issue 6 (2nd September 2013) - Blount, Jacob R.; Wu, James K.; Martinez, Matthew W.
Abstract A 46‐year‐old male was diagnosed with hypertrophic cardiomyopathy (HCM) and severe left ventricular outflow tract (LVOT) obstruction. Genetic testing revealed that this was a "mimic of HCM" and the true diagnosis was Fabry's disease, although there were no other clinical features of Fabry's. Despite maximal medical therapy he remained symptomatic from the outflow tract gradient and required surgical myectomy for symptom relief. This case illustrates the diagnosis of an HCM mimic by genetic testing. doi: 10.1111/jocs.12209 (J Card Surg 2013;28:695–698)